Sonographic Assessment of the Optic Nerve Sheath and Transorbital Monitoring of Treatment Effects in a Patient with Spontaneous Intracranial Hypotension: Case Report. Issue 2 (1st September 2011) - Bäuerle, Jochen; Gizewski, Elke R.; Stockhausen, Kerstin von; Rosengarten, Bernhard; Berghoff, Martin; Grams, Astrid E.; Kaps, Manfred; Nedelmann, Max
<x xml:space="preserve">Abstract</x> ABSTRACT OBJECTIVE To investigate the potential of the ultrasound‐based evaluation of the optic nerve sheath in a patient with spontaneous intracranial hypotension due to cervical cerebrospinal fluid (CSF) leakage. METHODS Repeated measurements of the optic nerve sheath diameter (ONSD) using B‐mode sonography were performed before treatment initiation, during medical treatment, and during a course of repeated placement of epidural blood patches. RESULTS On admission, transorbital sonography revealed a decreased ONSD of 4.1 mm on the right and 4.3 mm on the left side. After 8 months of treatment with caffeine and computed tomography‐guided epidural blood patches a gradual distension of the ONSD into the normal range was bilaterally observed (right: 5.2 mm; left: 5.3 mm). CONCLUSIONS The ultrasound‐based evaluation of the optic nerve sheath may be helpful in detecting CSF hypovolemia and for determination of treatment effects. This report should be seen as a basis for future investigations on the sonographic assessment of the optic nerve sheath in diagnosis and treatment of intracranial hypotension.